Revisionismos e negacionismos sobre a ditadura civil-militar no Brasil (2019-2022) - Macêdo, Paulo César (2022)
Our intention is to study and analyze revisionist and negationism propagated, during the Bolsonaro’s government, orchestrated by governist politicians and Bolsonaro coreligionists. These people defend, justify or deny the 1964 coup and agree with the state policies implemented by the civil-military dictatorship. This research aims to confront and deconstruct such narratives through the reflection about the construction of memories of the dictatorship in contemporary Brazil, using the History of the Present, also the relationship between Memory and History. For that, excerpts from speeches and interviews with a revisionist and negationist content of the current president in Brazil, Jair Messias Bolsonaro and some of his co-religionists were compared with excerpts from works by historians and intellectuals who studied the period in a critical way. Therefore, we seek to stimulate a discussion about the permanence and rupture of the military regime in public spaces with students, from that we aim to promote a critical reflection on the past period and the present. Finally, a pedagogical material was produced in the form of a sticker album, with excerpts from speeches, interviews, official notes, historiographical texts and images about some of the main content discussed about the1964-1985, in order to allow the functionality of the material produced, so that students can exercise their criticism in a responsible and ethical way. The material will be available to be used by students and teachers of the basic education.